"Jagged Edges": Victim Blaming, Student Care, and Legally Defensible Sexual Assault Investigations. Issue 3 (27th May 2017) - Best, Neil A.; Jun, Alexander
ABSTRACT: Victims and survivors of sexual violence are sometimes blamed for the assault because of irrelevant factors such as how much they had to drink or what they wore. Research has indicated that conservative religious beliefs increase the prevalence of victim blaming. In order to see if this pattern extended to college administrators, we used a hermeneutic phenomenological approach and interviewed eight sexual assault investigators at a faith-based institution to understand their lived and shared experiences. Four significant themes emerged from our study: the tension between student care and a legally defensible process, hope amid a never-ending saga, forbidden knowledge, and victim blaming. We conclude with a call to focus more carefully on language used, recommendations for decreasing the prevalence of victim blaming, and on preventing investigators from compassion fatigue, vicarious traumatization, and burnout.